Mathematical model of acceleration of three-shaft turbofan engines with coaxial propellers - Панін, В. В. (Proceedings of National Aviation University (archive), 1998)
Given is mathematical model of turbo propeller fan engine which takes into account the influence of gasdynamic unsteadies intended for diagnosing air engines on transitive modes